HUBUNGAN PENERAPAN KEWASPADAAN TERHADAP OBAT HIGH-ALERT DENGAN KEJADIAN MEDICATION ERRORS DI MURNI TEGUH MEMORIAL HOSPITAL MEDAN - Lady Noveline Sofiani Pasaribu; Seriga Banjarnahor (PT. Hasba Edukasi Mandiri, 2025)
Background: Medication error is any preventable event, that in inappropriate medication use (harm to the patient) when the medication is under the control of the health care professional, patient, or consumer. The classification of medication errors includes prescribing errors, dispensing errors, medication preparation errors, administration errors, and monitoring errors. High-alert drugs are drugs that have a high risk of causing major harm to patients if not used appropriately. High-alert drugs are several drugs that can harm patients if the drug is used incorrectly. The general principles for handling high-alert drugs are storage, prescribing, drug preparation/distribution, and drug administration. The most effective treatment for high-alert drugs is by reducing errors in administering high-alert drugs. To monitor high-alert drugs,